Highly Effective Lead Ion Adsorption by Manganese-Dioxide-Supported Core-Shell Structured Magnetite - Zhang, Haipeng; Chen, Shiyong; Shan, Yuhua; Qian, Xiaoqing; Yang, Yanju; Wang, Juanjuan (Frontiers in Environmental Science, 2022)
In this research, a magnetic core-shell composite, consisting of a Fe3O4 core and a silica shell (called Fe3O4@SiO2), was developed and then functionalized via MnO2 grafting at different MnO2 deposition levels (termed Fe3O4@SiO2-MnO2). The resulting materials were characterized by X-ray fluorescence, X-ray diffraction, a vibration sample magnetometer, transmission electron microscopy, N2 adsorption-desorption, zeta-potential studies and X-ray photoelectron spectroscopy. Visualizations showed that Fe3O4@SiO2-MnO2 had a magnetite core with size of 100 nm, overlaid by a rough silica shell and a relatively loose MnO2 deposition. The Pb(II) adsorption onto the composites was also assessed. It was found that MnO2 deposition on the Fe3O4@SiO2 surface enhanced Pb(II) adsorption, and the Pb(II) adsorption amount was highly correlated to the MnO2 deposition level. The adsorption kinetics of Pb(II) followed pseudo-second-order kinetics, and the adsorption rate could be decreased by increasing the initial concentration of Pb(II). A higher pH resulted in enhanced Pb(II) adsorption, which slightly increased with the coexistence of Na+ and Ca2+, along with the presence of dissolved humic acid. The adsorbent could easily be separated and recovered under the action of the external magnetic component and it displayed stable adsorption behaviour over four adsorption-desorption periods. The results emphasize the high potential of Fe3O4@SiO2-MnO2 materials for the adsorptive removal of Pb(II) in water.